Preparatory endonasal surgical modification to create a functional corridor for effective photoimmunotherapy in residual nasopharyngeal carcinoma: a case report - Ishida, Yoshiya; Watanabe, Akihito; Miyakoshi, Kaoru; Hayashi, Shuto; Hangai, Masato; Miyazaki, Kosuke; Hashimoto, Ruka; Wada, Tetsuji (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2026)
Delivering effective photoimmunotherapy (PIT) in the anatomically constrained nasopharynx is technically challenging. Optimizing laser access is essential for achieving complete tumor illumination and maximizing treatment efficacy. A man in his fifties with refractory residual nasopharyngeal carcinoma (NPC) underwent preparatory endonasal surgical modification consisting of endoscopic resection of the posterior nasal septum and inferior turbinates. This procedure created a straight transnasal functional corridor and provided an adequate standoff distance for frontal diffuser placement. PIT was subsequently administered using intravenous cetuximab sarotalocan sodium, according to the standard protocol. The newly established functional corridor enabled stable and uniform laser illumination of the nasopharyngeal lesion. The procedure was completed without intraoperative or postoperative complications. Endoscopy and biopsy performed seven weeks after PIT confirmed a complete response, and the patient remained disease-free at 12 months of follow-up. Preparatory endonasal surgical modification can overcome anatomical barriers and facilitate safe and effective PIT delivery for residual NPC. By simplifying laser access and reducing technical demands, this minimally invasive approach may facilitate broader clinical use of PIT in anatomically constrained nasopharyngeal regions.